This might hurt [large type] - Wrobel, Stephanie (Thorndike Press large print core series., 2022)
"Natalie Collins hasn't heard from her sister in more than half a year. The last time they spoke, Kit was slogging from mundane workdays to obligatory happy hours to crying in the shower about their dead mother. And then she found Wisewood. On a private island off the coast of Maine, Wisewood's guests commit to six-month stays. During this time, they're prohibited from contact with the rest of the world. Natalie receives a menacing e-mail from a Wisewood account threatening to reveal the secret she's been keeping from Kit. Natalie hurries north to come clean to her sister and bring her home. but she's about to learn that Wisewood won't let them go without a fight"--